Forecasting Ocean Mesoscale Eddies in the Northwest Pacific in a Dynamic Ocean Forecast System - Jiakang Zhang; Hailong Liu; Mengrong Ding; Yao Meng; Weipeng Zheng; Pengfei Lin; Zipeng Yu; Yiwen Li; Pengfei Wang; Jian Chen (Journal of Marine Science and Engineering, 2025)
The LICOM Forecast System (LFS), a global eddy-resolving ocean forecasting system, provides 1–15-day forecasts of ocean mesoscale eddies (OMEs). This study conducts a comparative analysis of the forecast results against observational data, thereby evaluating the performance of the LFS. Results show that LFS underestimates the number of eddies by ~10% and their amplitude by ~30%, while overestimating eddy radius by ~5% and velocity by ~25%. Forecasted eddies are matched on a one-to-one basis with observed eddies based on distance, ensuring that those forecasted eddies that can locate corresponding counterparts in the observational dataset yield accurate forecasts. The outcomes reveal that the LFS successfully forecasts 63% of the eddies in the NWP. The characteristics of these accurately forecasted eddies are delineated. The findings indicate that eddies with greater amplitudes are more likely to be accurately predicted. Additionally, we further scrutinized the correlation between eddy attributes and forecast performance, revealing that with an increase in amplitude or a decrease in velocity, the LFS produces forecasts with improved locational accuracy. The mean forecast error in eddy position is 79.94 km for a 1-day lead time, which decreases to 70.97 km for eddies with amplitudes exceeding 1 cm and velocities below 1 km/day.